Analysis of influence of environmental crisis in the Lake Urmia Basin on the Middle East - Jannatov, Asim Jannatoglu (Penerbit UKM, 2024)
Although all of the existing water resources and lakes in the world are not suitable for agriculture, their preservation plays a very decisive role in preventing environmental disasters. Unfortunately, water sources in many countries are not strictly protected and are in danger of drying up as a result of artificial factors. Lake Urmia located between East and West Azerbaijani provinces in Iran is one of these lakes. Since the 1990s of the last century, the water level in Lake Urmia, which is considered one of the largest lakes in the world in terms of salinity, has decreased and is currently facing the threat of drying up. The complete drying of the lake will not only damage the ecosystem in the region, its side effects may also manifest in neighboring countries and the whole Middle East region. This process will also accelerate the migration flow from the region to other provinces and neighboring countries. Thus, the lake crisis in Urmia is hazardous for the entire region. The purpose of this study is to reveal the main causes of drying lake, predict threats emerging in the region and look for solutions to eliminate this crisis.